The effects of combined balance and plyometric training on change-of-direction and dynamic balance: A meta-analysis - Guang Feng; Ruobing Chen; Chonghui Wu; Yongfeng Liu (PLoS ONE, 2026)
Background Preceding studies have demonstrated that a combination of balance and plyometric training can enhance change-of-direction and dynamic balance. However, to date, a paucity of meta-analyses has precluded the provision of a comprehensive summary of the extant data. Objective The meta-analysis aims to examine the effects of combined balance and plyometric training on change-of-direction and dynamic balance compared to active controls. Method The present meta-analysis was conducted in strict adherence to the PRISMA 2020 guidelines. A systematic search was conducted in five electronic databases: PubMed, Web of Science, Scopus, Embase, EBSCOhost. The present study incorporated studies published from inception until June 2025. Eligibility was assessed using the PICOS method. The quality of studies was assessed using the Cochrane risk of bias assessment tool. For the meta-analysis, the random-effects model was utilised, and the Hedges’ g effect size (ES) and its 95% confidence interval (95% CI) were reported. Subgroup analyses were conducted (age, gender, training frequency, duration). Results A total of 10 studies with 270 participants were included. Compared with the control group, combined balance and plyometric training significantly improved change-of-direction (ES = −0.77, I 2 = 65.6%, P < 0.05), Y-Balance (ES = 1.32, I ² = 67.5%, P < 0.05), dynamic postural stability index (ES = −1.27, I² = 0.0%, P < 0.05), and center of pressure (ES = −1.25, I ² = 58.8%, P < 0.05). Subgroup analysis showed that age, gender, training frequency, and duration had no effect on the training effect of change-of-direction. Conclusions Combined balance and plyometric training can significantly improve change-of-direction and dynamic balance, and existing evidence shows that the training effects of change-of-direction are not affected by age, gender, training frequency, or duration.